2016
DOI: 10.1007/s00068-016-0690-5
|View full text |Cite
|
Sign up to set email alerts
|

The clinical results of a novel method for minimal invasive dynamic hip screw fixation of intertrochanteric fractures compared to the conventional one

Abstract: The new MIDHS technique is a trustable procedure that may help the surgeon to perform DHS fixation in a proper way. It offers a better motoric function, less pain. However, further studies should be conducted to evaluate the validity of such radiological land marks in proximal femoral surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…It had been demonstrated that, using this novel angle and landmarks produced even smaller incision than the well-known minimal invasive DHS technique and a more superior clinical results than the conventional technique 12 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It had been demonstrated that, using this novel angle and landmarks produced even smaller incision than the well-known minimal invasive DHS technique and a more superior clinical results than the conventional technique 12 .…”
Section: Discussionmentioning
confidence: 96%
“…The clinical results of minimal DHS using the new angle were compared to the clinical results using the conventional technique were evaluated 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Variable radiological measures have been introduced to help radiologists and orthopedic surgeons to diagnose diseases, evaluate surgeries, and plan for surgical interventions (2)(3)(4). By introduction of picture archiving and communication systems (PACS) which became widespread and the standard radiological viewing tool in many orthopedic clinics, radiologists and orthopedic surgeons became more able to measure angles and distances even in a more precise manner (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Many radiological parameters have been introduced in the literature to aid in diagnosis and surgical interventions (4,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Many studies have correlated the Manchester scale system with variant foot angles in HV deformity, including the intermetatarsal and metatarsophalangeal angles. 12,13 However, it is strange not to find a well-structured study in the literature focusing the impact of the medial cuneiform bone variant measures (lateral tilt, the first metatarsocuneiform slope angle (MCSA) and the first metatarsocuneiform angle (MCA)) on the HV different clinical severity using the Manchester scale.…”
Section: Introductionmentioning
confidence: 99%